A new method of reinforcing graphene nanoplatelets in glass/epoxy composites - Khurshid, Malik; Ahmad, Faiz; Yunus, Nurul Azhani; Nakato, Teruyuki; Mouri, Emiko; Shaik Dawood, Mohd. Sultan Ibrahim; Memon, I (2022)
This research aims to develop a method for the amalgamation of graphene nanoplatelets in glass/epoxy composites. The poor interface bonding between the fiber and matrix is critical and hinders the full performance of the composites. Glass fabric and epoxy were used as reinforcement and matrix in the composite, respectively. Graphene nanoplatelets were utilized as an additional nano-materials filler for the composites. Glass/graphene/epoxy and glass/epoxy composites were fabricated via vacuum infusion molding. The new method of applying graphene nanoplatelets as secondary reinforcement in the composite was developed based on proper functionalization in the sonication process. The physical, tensile, flexural, and short beam interlaminar properties of fabricated composites were examined to analyze the method’s effectiveness. The results showed that density decreased by around 5%; however, thickness increased by around 34% after introducing graphene nanoplatelets into the composites. The tensile strength and modulus of the composites declined by approximately 19%, on the other hand, flexural strength and modulus increased by around 63.3% and 8.3%, respectively, after the addition of graphene nanoplatelets into the composites. Moreover, the interlaminar shear strength of the composite was enhanced by approximately 50%.